Respiratory perspective of COVID-19 in pregnancy - Arini Purwono; Heidy Agustin; Yuyun Lisnawati; Hana Khairina Putri Faisal (Journal of Infection in Developing Countries)
The coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was declared a global pandemic in March 2020 by the World Health Organization (WHO). By February 2022, the disease had infected more than 500 million people globally. COVID-19 frequently manifests as pneumonia and mortality is mainly caused by acute respiratory distress syndrome (ARDS). Previous studies have reported that pregnant women are at a higher risk of SARS-CoV-2 infection and complications can happen due to alterations in the immune response, respiratory physiology, hypercoagulable state, and placental pathology. Clinicians face the challenge of selecting the proper treatment for pregnant patients with different physiological characteristics compared with the non-pregnant population. Furthermore, drug safety for both the patient and the fetus should also be considered. Efforts to prevent COVID-19, including prioritizing vaccination for pregnant women, are essential to break the chain of COVID-19 transmission in the pregnant population. This review aims to summarize the current literature regarding the effect of COVID-19 in pregnant women, its clinical manifestations, treatment, complications, and prevention.